What Kind of Parents Are You?: The Discussion of Expectations for Parents in the Press Coverage of the Lindbergh Kidnapping. Issue 3 (1st October 2016) - Bernhardt, Mark
Abstract : The Lindbergh kidnapping was a media spectacle. In the initial kidnapping reports, newspapers described the Lindberghs in sympathetic terms, as a family torn apart by the scourge of kidnapping that plagued the nation as a result of organized crime's seemingly unchecked power. Then, after the third day, with the Lindberghs under close scrutiny because of the investigation's unprecedented coverage due to their celebrity and the intense debate about how to address the nation's kidnapping problem, politicians, law enforcement officials, public figures, and the papers began publicly critiquing some of the Lindberghs' actions before, during, and after the night of the kidnapping. The papers served as a forum for assessing whether the Lindberghs should be deemed good parents, and the ensuing debate exposed gender and class tensions resulting from recent social and economic changes that threatened to undermine the parenting standards embraced by the era's dominant culture.